Relationship between α7 nAChR and apoptosis in human lymphocytes - de Rosa, Maria Jose (2005)
The presence of nicotinic receptors (nAChRs) in blood cells has been demonstrated. However, little is known about their functional roles. We have detected mRNA of a7 nAChR in peripheral human lymphocytes and determined that its expression is highly variable among individuals and within the same individual at different times. Upregulation of a7 is systematically observed after incubation of lymphocytes with nicotine or a-bungarotoxin. In addition, the incubation with these drugs decreases the percentage of apoptotic cells induced by the exposure to cortisol. Our results suggest that a7 nAChRs are involved in the modulation of cortisol-induced apoptosis.